2021
DOI: 10.1038/s41598-021-90060-6
|View full text |Cite
|
Sign up to set email alerts
|

The modulatory effects of alfalfa polysaccharide on intestinal microbiota and systemic health of Salmonella serotype (ser.) Enteritidis-challenged broilers

Abstract: Salmonella serotype (ser.) Enteritidis infection in broilers is a main foodborne illness that substantially threatens food security. This study aimed to examine the effects of a novel polysaccharide isolated from alfalfa (APS) on the intestinal microbiome and systemic health of S. ser. Enteritidis-infected broilers. The results indicated that broilers receiving the APS-supplemented diet had the improved (P < 0.05) growth performance and gut health than those fed no APS-supplemented diet. Supplementation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Plant-derived polysaccharides (PS) are a kind of macromolecular polymer synthesized in plants, which plays many vital roles in maintaining the integrity of cells and in imparting resistance against abiotic stress in plants. 1,2 As a functional food/ feed for humans and animals, phytogenic PS exhibit a variety of bioactivities, 3,4 including antioxidative capacity, 5,6 antiinflammation, 7,8 immunomodulation, 9 and growth-promotion. 10 Homogeneous PS are composed of a single kind of monomer by glycosidic bonding, whereas hetero-PS comprise polymers of several kinds of monosaccharides or uronic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Plant-derived polysaccharides (PS) are a kind of macromolecular polymer synthesized in plants, which plays many vital roles in maintaining the integrity of cells and in imparting resistance against abiotic stress in plants. 1,2 As a functional food/ feed for humans and animals, phytogenic PS exhibit a variety of bioactivities, 3,4 including antioxidative capacity, 5,6 antiinflammation, 7,8 immunomodulation, 9 and growth-promotion. 10 Homogeneous PS are composed of a single kind of monomer by glycosidic bonding, whereas hetero-PS comprise polymers of several kinds of monosaccharides or uronic acids.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary Achyranthes bidentata polysaccharide supplementation increased body weight and average daily weight gain of broilers challenged with Escherichia coli K88 (14). It was also reported that Salmonella serotype Enteritidis-infected broilers exhibited impaired growth performance, but this was relieved by diets supplemented with polysaccharides isolated from alfalfa (24). Additionally, the biological activities of polysaccharides are closely related to their molecular weight and specific spatial structures (25).…”
Section: Performance Productivitymentioning
confidence: 91%
“…Polysaccharide supplementation decreased the content of D-lactic acid and the activity of diamine oxidase in the serum, implying that polysaccharides improved the intestinal permeability and protected the intestinal barrier function (35). Accordingly, accumulated evidences showed that polysaccharides improved the intestinal integrity, maintained the integrity of intestinal epithelium, and upregulated mRNA expressions or protein abundances of tight junction proteins such as ZO-1, occludin, and claudin-1 in the jejunum and ileum of broilers in normal or stressed conditions (12,24,44). It was generally reported that polysaccharides could not be absorbed through the intestinal mucosa into the body, so the health benefits of polysaccharides were rooted in their effects on the intestinal mucosal immune system (49).…”
Section: Gut Health and Intestinal Muscosal Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the above normal feeding conditions, plant-derived polysaccharides could also play a role in poultry under challenging conditions such as pathogen growth. When broilers are infected with Salmonella serotype resulting in enteritis, a dietary addition of 500 mg/kg alfalfa polysaccharides enhanced the abundance of beneficial microorganisms in the intestinal tract, such as Bacteroides , Barnesiella , Parabacteroides , Butyricimonas , Prevotellaceae while decreasing facultative anaerobic bacteria, including Proteobacteria , Actinomycetes , Ruminococcaceae , Lachnospiraceae and Burkholdeaceae [ 34 ]. Moreover, Cui et al [ 35 ] found that dietary Caulis Spatholobi polysaccharide (0.2, 0.4, and 0.6%) increased cecum species richness, restored cyclophosphamide-induced intestinal microbiota imbalance, and improved Lactobacillus abundance.…”
Section: Effects Of Plant-derived Polysaccharides On Intestinal Barri...mentioning
confidence: 99%